PELATIHAN KONPREHENSIF: STRATEGI BERKELANJUTAN PEMBUDIDAYA IKAN LELE MELALUI SISTEM GREEN DAN RED WATER SYSTEM - Suhendra, Suhendra; Desliyanah, Sherly; Padri, Syahrul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
This research aims to develop a comprehensive training program for catfish farmers, focusing on the integration of Green Water System (GWS) and Red Water System (RWS) Techniques to achieve sustainable catfish farming. The research methods used include field surveys, primary and secondary data collection, and statistical analysis. The aim of this study was to identify the main challenges faced by catfish farmers and design appropriate training programs to address those issues. In addition, this study aims to understand the benefits of applying GWS and RWS techniques in catfish farming. The results showed that catfish farmers face several problems, such as poor water quality, fish diseases, and low feed efficiency. The comprehensive training program developed involves a series of modules covering an understanding of the basic principles of GWS and RWS, water quality management, fish disease control, and improving feed efficiency. Through the implementation of this training program, catfish farmers can improve water quality in aquaculture ponds using GWS techniques, which involve the use of aquatic plants to help clean the water and improve environmental quality for fish. In addition, by applying RWS techniques, cultivators can optimize feed use, reduce feed waste, and improve feed efficiency. It is expected that the development of this comprehensive training program will help catfish farmers in increasing aquaculture productivity, reducing losses due to fish diseases, and maintaining the sustainability of catfish farming businesses. This training program can be a practical guide for catfish farmers in applying GWS and RWS techniques for sustainable catfish farming in the future.